High-resolution infrared spectroscopy of naphthalene and acenaphthene dimers. (17th January 2021) - Lemmens, Alexander K.; Chopra, Pragya; Garg, Diksha; Steber, Amanda L.; Schnell, Melanie; Buma, Wybren Jan; Rijs, Anouk M.
Abstract : Non-covalent interactions are rapidly gaining interest as they are often crucial in determining the properties of materials, and key to supramolecular chemistry and to biochemistry. Non-covalent Polycyclic Aromatic Hydrocarbon (PAH) complexes are in particular relevant to astrochemistry and combustion chemistry where they are involved in the initial steps of condensation and soot formation, respectively. Here, we investigated non-covalent π-π stacking and CH-π interactions in naphthalene and acenaphthene clusters using high-resolution IR-UV spectroscopy in combination with quantum chemical calculations. We identified spectral shifts that occur upon complexation and thereby evaluated predicted potential energy surfaces. Although theory predicts a blueshift, a redshift is observed for the aliphatic CH-π interactions in the experimental spectrum of acenaphthene upon dimerization, indicating that CH-π interaction indeed affects the aliphatic bonds, while a blueshift is predicted, consequently theory deserves attention here. The results provide strong indications for a prevalent parallel naphthalene dimer, showing that π-π stacking interactions become significant for bicyclic and larger PAHs. GRAPHICAL ABSTRACT: